Investment opportunity set, product mix, and the relationship between bank CEO compensation and risk-taking - III Elijah Brewer; William Curt Hunter; III William E. Jackson (Federal Reserve Bank of Atlanta, 2004)
The product mix changes that have occurred in banking organizations during the 1990s provide a natural experiment for investigating how firms adjust their executive compensation contracts as their mix of businesses changes. Deregulation and new technology have eroded banking organizations' comparative advantages and have made it easier for nonbank competitors to enter banking organizations' lending and deposit-taking businesses. In response, banking organizations have shifted their sale mix toward noninterest income by engaging in municipal revenue bond underwriting, commercial paper underwriting, discount brokering, managing and advising open- and close-ended mutual funds, underwriting mortgage-backed securities, selling and underwriting various forms of insurance products, selling annuities, and other investment banking activities via Section 20 subsidiaries. These mix changes could affect firms' risk and the structure of CEO compensation. The authors find that as the average banking organization tilts its product mix toward fee-based activities and away from traditional activities, equity-based compensation increases. They also find that more risky banks have significantly higher levels of equity-based compensation, as do banks with more investment opportunities. But, more levered banks do not have higher levels of equity-based CEO compensation. Finally, the authors observe that equity-based compensation is more important after the Riegle-Neal Act of 1994.
Keywords: 330; Corporate Governance; Führungskräfte; Vergütungssystem; Produktmanagement; Bankrisiko; USA